Vegetables- and antioxidant-related nutrients, genetic susceptibility, and non-Hodgkin lymphoma risk - Kelemen, Linda E. (2008)
Genetic susceptibility to DNA oxidation, carcinogen metabolism, and altered DNA repair may increase non-Hodgkin lymphoma (NHL) risk, whereas vegetables-and antioxidant-related nutrients may decrease risk. We evaluated the interaction of a priori-defined dietary factors with 28 polymorphisms in these metabolic pathways. Incident cases (n = 1,141) were identified during 1998–2000 from four cancer registries and frequency-matched to population-based controls (n = 949). We estimated diet-gene joint effects using two-phase semi-parametric maximum-likelihood methods, which utilized genotype data from all subjects as well as 371 cases and 311 controls with available diet information. Adjusted odds ratios (95% confidence intervals) were lower among common allele carriers with higher dietary intakes. For the GSTM3 3-base insertion and higher total vegetable intake, the risk was 0.56 (0.35–0.92, p interaction = 0.03); for GSTP1 A114V and higher cruciferous vegetable intake, the risk was 0.52 (0.34–0.81, p interaction = 0.02); for OGG1 S326C and higher daily zinc intake, the risk was 0.71 (0.47–1.08, p interaction = 0.04) and for XRCC3 T241M and higher green leafy vegetable intake, the risk was 0.63 (0.41–0.97, p interaction = 0.03). Calculation of the false positive report probability determined a high likelihood of falsely positive associations. Although most associations have not been examined previously with NHL, our results suggest the examined polymorphisms are not modifiers of the association between vegetable and zinc intakes and NHL risk.